Determinants of Household Healthcare Choice Behavior: A Study in Purulia District, West Bengal (International Journal of Innovative Research in Engineering & Management, 2022)
A well organised healthcare system is  one of the pillars of a society’s social and economic  infrastructure. Efficient healthcare system is one of the  important indicators of development. In times of global  epidemics Covid-19 healthcare seeking behaviour has  become an important issue. People adjust their treatment  modalities based on the health system. Poor families in  particular have very limited access to medical care; they  usually rely on government medical facilities because  they cannot afford private treatment. On the other hand,  even in rural areas, access to medical care limited due to  lack of additional healthcare facilities. Therefore in rural  area’s it is very important to diagnose the factors that  influence the health seeking behaviour of the household. The Specific objectives of the study are to investigate  health status of households across Purulia district using  secondary data from NFHS- 4 (2015-2016) and to  determine the factors that influencing health seeking  behaviour of the sample households. We have visited  randomly selected three villages of Kashipur block in  Purulia district, West Bengal and surveyed two hundred  households. To determine the factors that influencing  household healthcare seeking behaviour we have fitted  logit model. The explanatory variables monthly average  family income, household head’s education, number of  members in a household above 60 years, number of  members in a household below 6 years, having at least  one member who consume medicines during the whole  year, effect of Covid-19 on income, effect of Covid-19 on  health, social category, village residence have positive  significant impact on the probability of household  members seeking treatment from both government and  private places. We consider ST as our base and find that  the general community has significant impact on the  household members receiving treatment from both  government and private places. From the result we find  that the major source of income of the sample households has no significant impact on the healthcare seeking  behaviour of sample households.
Keywords: Health seeking behaviour; medical care; NFHS- 4; Kashipur block; Logit model